The Bahamas : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights the continued weak economic activity in The Bahamas in 2016. Hurricane Matthew, which hit The Bahamas in October 2016, significantly impacted tourism activity in 2016 and early 2017. However, completion of the megaresort Baha Mar and posthurricane reconstruction activity gave a boost to job creation: the unemployment rate declined to 9.9 percent in May 2017. Real GDP growth is projected to pick up to 1.75 percent in 2017 and to 2.5 in 2018, driven by a stronger US economy, the phased opening of Baha Mar, and related construction activity. However, medium-term growth would remain low, reflecting significant structural bottlenecks.